(untitled) (Acta Scientiarum. Biological Sciences, 2021)
This study aimed to assess the occurrence of arbuscular mycorrhizal fungi (AMF) in annatto (Bixa orellana L.) cultivars and their response to AMF inoculation using biometric parameters. The occurrence surveys were conducted in annatto fields in three municipalities from Pernambuco Forest Zone: Lagoa de Itaenga, Gloria de Goitá, and Vitoria de Santo Antão, and in four cultivars (Red Piave, Green Piave, Red Peruvian Paulista, and Green Peruvian Paulista). In a greenhouse, biometric parameters of annatto seedlings of Red Piave, Red Peruvian Paulista, Embrapa-36, and Embrapa-37 cultivars inoculated with AMF isolated from annatto fields. The Red Piave cultivar exhibited greater root colonization than the Green Peruvian Paulista in the Lagoa de Itaenga and Vitoria de Santo Antão municipalities. The cultivar Red Piave showed a more beneficial association with AMF in plants and soil than cultivar Green Peruvian Paulista did, in both Lagoa de Itaenga and Vitoria de Santo Antão. AMF inoculation was effective in promoting the growth of annatto plants, particularly those inoculants with S. heterogama and C. etunicatum.